أبعاد التفكير الابداعي في ظل المتغيرات المُعدِّلة لدى تلاميذ السنة الثالثة ثانوي بالأغواط - عطاوة, سليم; قويدري, لخضر (جامعة الوادي - University of Eloued, 2020)
تهدف هذه الورقة إلى دراسة أبعاد التفكير الإبداعي (الطلاقة-المرونة-الأصالة) في ظل المتغيرات المُعدِّلة (الجنس-الشعبة) لدى تلاميذ، ولتحقيق هذا الهدف تمّ تطبيق اختبار تورانس للتفكير الإبداعي الصورة (أ) اللفظية على عيّنة من تلاميذ القسم النهائي بمدينة الأغواط حجمها 120 تلميذ. وقد أظهرت النتائج المتحصل عليها وجود فروق ذات دلالة إحصائية في بعدى الطلاقة والأصالة لصالح الإناث، وعدم وجود فروق ذات دلالة إحصائية في بعد المرونة بين الجنسين، كما أظهرت النتائج وجود فروق ذات دلالة إحصائية في أبعاد التفكير الإبداعي الثلاثة (الطلاقة والمرونة والأصالة) لصالح التلاميذ قسم العلمي. Abstract: The purpose of this article is to study the dimensions of creative thinking (fluidity- flexibility- originality) in light of the modelator variables(sex and specialization) of students. To achieve this goal, Torrance Tests of Creative Thinking (Form A) was applied to a sample of(120) terminal students of high schools in Laghouat city. The results showed statistically significant differences in the dimensions of fluidity and originality in favor of women, with no statistically significant difference in flexibility between the sexes, as well as statistically significant differences in the two dimensions of creative thinking The fluidity and the originality of women and the absence of gender differences in flexibility. The results also showed statistically significant differences in the dimensions of creative thinking and the superiority of students in the scientific class.
مقال
Keywords: اختبار تورانس اللفظي الصورة (أ)؛ الطلاقة؛ المرونة؛ الأصالة؛ الجنس؛ الشعبة; TTCT Form(A); Fluency; Flexibility; Originality; Gender; Division